PENERAPAN ETIKA BISNIS DAN PROFESI DALAM UPAYA PENINGKATAN KUALITAS PELAYANAN SKCK POLSEK SIDOARJO KOTA MELALUI INOVASI PROGRAM SURVEI ONLINE (EPZI) - Gabriele Marelda Yafed; Agus Subandoro (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research aims to determine the application of business and professional ethics, especially in the field of service professions. In the public service book written by Semil,N (2018), a public servant must have the ability and integrity in serving the community in order to create good judgment and the formation of a professional work. The research method used in this study is descriptive quantitative. This research will discuss problems by collecting, reviewing and describing a data obtained through observation and processing existing data, then described so that it can become an understanding for readers. The results of this study, it shows that the Sidoarjo City Police applies professional ethics as an evaluation material for improving service quality and has implemented it in accordance with public service standards that have been set by the government in Law Number 25 of 2009 concerning Public Services.